2017
DOI: 10.1097/cmr.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

The role of 5-hydroxymethylcytosine in melanoma

Abstract: Malignant melanoma is a highly aggressive neoplasia of melanocytic origin. In part because of the lack of effective treatment methods, the incidence and mortality rates of this disease continue to increase. Rapidly accumulating evidence suggests that dysregulation of epigenetic mechanisms, including DNA methylation/demethylation, chromatin modification, and remodeling, and diverse activities of noncoding RNAs, play a central role in the pathogenesis of melanoma. The epigenetic mark 5-hydroxymethylcytosine (5-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In addition to the study by Lian CG et al, 5-hmC expression has been evaluated in several studies in cutaneous melanocytic proliferations [ 15 , 16 , 17 ]. Our results are in line with these studies, which showed a significant loss of 5-hmC in melanomas compared to nevi [ 18 ]. In the study by Larson AR et al [ 15 ], 5-hmC loss was evaluated by immunohistochemistry in a group of 175 cases including 18 benign cutaneous nevi, 20 dysplastic nevi, 10 atypical Spitz nevi, 20 borderline tumors, 5 cutaneous melanomas developing from nevi and 102 primary cutaneous melanomas.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the study by Lian CG et al, 5-hmC expression has been evaluated in several studies in cutaneous melanocytic proliferations [ 15 , 16 , 17 ]. Our results are in line with these studies, which showed a significant loss of 5-hmC in melanomas compared to nevi [ 18 ]. In the study by Larson AR et al [ 15 ], 5-hmC loss was evaluated by immunohistochemistry in a group of 175 cases including 18 benign cutaneous nevi, 20 dysplastic nevi, 10 atypical Spitz nevi, 20 borderline tumors, 5 cutaneous melanomas developing from nevi and 102 primary cutaneous melanomas.…”
Section: Discussionsupporting
confidence: 93%
“…These include reduced survival rates and an increased risk of disease recurrence. Melanoma is a highly aggressive form of skin cancer, exhibiting a significant loss of 5-hmC levels at all stages of melanomas, including primary melanomas, metastases, conjunctival melanomas, mucosal melanomas, and sentinel lymph node biopsies [14]. Merely acral melanoma did not show a significant loss of expression 5-hmC.…”
Section: Introductionmentioning
confidence: 92%
“…Oncometabolite 2-HG also inhibits the function of ten-eleven translocation (TET) enzymes, which are responsible for converting 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC). It competes with 2-OG for binding to the active site of 2-OG-dependent oxygenase [ 11 , 12 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%